The Effect of Role Playing Strategy on Students’ Speaking Ability At Eighth Grade of SMP Negeri 9 Pematangsiantar - Ridwin Purba; Cindy Nirvana Aritonang (Program Studi Pendidikan Bahasa Inggris FKIP, 2022)
The objective of this research was to find the effect of role play strategy on students’ speaking ability at eighth grade of SMP Negeri 9 Pematangsiantar.This research was conducted at SMP Negeri 9 Pematangsiantar with method of this research used quantitative methhod with true experimental method. Population of this research was eighth grade students and sample of this research was two class of eighth grade divide into control and experimental class that consist of 64 students. The technique of collecting data was pre-test and post-test. The technique of analyzing data was use SPSS version 21.0. The result of this test. If the tcount value is higher than the ttable at the significance level 0.05 and the degree fredoom (df) N-1, thus the alternative hypothesis (Ha) was accepted and null hypothesis (Ho) is rejected. The researcher found that tcount 4.50 > ttable 1.66 at significance level 0.05 with the degrees of fredoom (df) (32-1=31) for each class so the degrees of freedom is 62. It means that Ho is rejected and Ha is accepted.Using role play strategy is able to develop the students’ speaking ability at the eighth grade students of Smp Negeri 9 Pematangsiantar. It can be seen in the result of the analysis data which shows that there is a significant progress between the students’ speaking ability before and after the researcher given the trearment. The score in experimental class is more significant increase than in control class because of the researcher give the treatment